Altered microRNAs related to synaptic function as potential plasma biomarkers for Alzheimer’s disease - Dolores Siedlecki-Wullich; Judit Català-Solsona; Cristina Fábregas; Isabel Hernández; Jordi Clarimon; Alberto Lleó; Merce Boada; Carlos A. Saura; José Rodríguez-Álvarez; Alfredo J. Miñano-Molina (Alzheimer’s Research & Therapy, 2019)
Abstract Background Several evidences suggest that failure of synaptic function occurs at preclinical stages of Alzheimer’s disease (AD) preceding neuronal loss and the classical AD pathological hallmarks. Nowadays, there is an urgent need to identify reliable biomarkers that could be obtained with non-invasive methods to improve AD diagnosis at early stages. Here, we have examined plasma levels of a group of miRNAs related to synaptic proteins in a cohort composed of cognitive healthy controls (HC), mild cognitive impairment (MCI) and AD subjects. Methods Plasma and brain levels of miRNAs were analysed in two different cohorts including 38 HC, 26 MCI, 56 AD dementia patients and 27 frontotemporal dementia (FTD) patients. D’Agostino and Pearson and Shapiro-Wilk tests were used to evaluate data normality. miRNA levels between groups were compared using a two-sided nonparametric Mann-Whitney test and sensitivity and specificity was determined by receiver operating characteristic curve analysis. Results Significant upregulation of miR-92a-3p, miR-181c-5p and miR-210-3p was found in the plasma of both MCI and AD subjects. MCI patients that progress to AD showed higher plasma levels of these miRNAs. By contrast, no changes in miR-92a-3p, miR-181c-5p or miR-210-3p levels were observed in plasma obtained from a cohort of FTD. Conclusion Our study shows that plasma miR-92a-3p, miR-181c-5p and miR-210-3p constitute a specific molecular signature potentially useful as a potential biomarker for AD.